The TRIANGLE operation for pancreatic head and body cancers: early postoperative outcomes - Klotz, Rosa; Hackert, Thilo; Heger, Patrick; Probst, Pascal; Hinz, Ulf; Loos, Martin; Berchtold, Christoph; Mehrabi, Arianeb; Schneider, Martin; Müller, Beat P.; Strobel, Oliver; Diener, Markus K.; et al. (HPB, 2022)
Background - Surgical resection is the mainstay of potential cure for patients with pancreatic cancer, however, local recurrence is frequent. Previously, we have described an extended resection technique for pancreatoduodenectomy aiming at a radical resection of the nerve and lymphatic tissue between celiac artery, superior mesenteric artery and mesenteric-portal axis (TRIANGLE operation). Until now, data on postoperative outcome have not been reported, yet. - Methods - Patients who underwent either partial (PD) or total pancreatoduodenectomy (TP) applying the TRIANGLE procedure were identified. These cohorts were compared to matched historic cohorts with standard resections. - Results - Overall, 330 patients were analysed (PDTRIANGLE and PDSTANDARD, each n = 108; TPTRIANGLE and TPSTANDARD, each n = 57). More lymph nodes were harvested in TRIANGLE compared to standard resection (PD: 27.5 (21-35) versus 31.5 (24-40); P = 0.0187, TP: 33 (28-49) versus 44 (29-53); P = 0.3174) and the rate of tumour positive resections margins, R1(direct), dropped. Duration of operation was significantly longer and blood loss higher. Postoperative mortality and complications did not differ significantly. - Conclusion - Pancreatoduodenectomy according to the TRIANGLE protocol can be performed without increased morbidity and mortality at a high-volume centre. Long-term survival and quality of life need to be investigated in prospective clinical trials with adequate sample size.
Available online 6 July 2021
Gesehen am 01.04.2022